Diesial Engine Oil Production 15W- 40 API CI-4 - الكعبي, رحيم عامر (Journal of Petroleum Research and Studies, 2021)
In the present study, the new oils were produced that compete with global oils, which reflects a positive economic return for the Middle Refineries Company and the reduction of imported oils in support of the national economy and the Iraqi product protection law with clarification of some basic terms and concepts for the production of ready-made oils, which enables knowledge of the main points of evaluating oils. As well as addressing the types of base oils from which ready-made oils are manufactured, the way to obtain base oils of different levels, and the production units. The reliance on research methods was on comparison with imported and manufactured oils according to international certificates and in coordination with the Research and Quality Control Department. Laboratory experiments were conducted with different proportions for mixing until the required results were reached and using laboratory devices to conduct the required tests to meet the international standards. Where several experiments were conducted by changing the mixing ratios between base oils (SN-150, SN-500). In addition, changing the percentage of additives of viscosity enhancer (VI) as well as changing the degree of pouring improver (PPD) while keeping the ratio of the improver constant (MX-2171). Which is wt. 13.6%. Final results were obtained for mixing ratios to obtain identical specifications for diesel engine oil in conformity with international specifications, where the ratio of the MX-5217 enhancer was around 13.6%, which is considered the main enhancer as well as the viscosity enhancer, the ratio was 3.0% and the spillage reduction ratio was 1.5%. For a mixture of base oils, it was for the base oil SN-150 up to 18.0% and for base oil SN-500, the percentage was 36.9% knowing that all the aforementioned percentages are weight ratios.